Existence solutions for second order Hamiltonian systems. (February 2016) - Li, Lin; Schechter, Martin
Abstract: We study the existence of periodic solutions for a second order non-autonomous dynamical system containing variable kinetic energy terms. Subquadratic problems and superquadratic problems are both considered.